Otimização de pórticos planos em concreto armado considerando restrições de cardinalidade - Boscardin, Juliana Triches (2017)
In the pre-dimensioning of structures, the engineer uses his experience and intuition to choose the elements that will best meet the aspects of safety and functionality, that is, the calculation made through a process of trial and error. This process does not always guarantee a choice of the most economical option, since there are several solutions to a given situation. The optimization techniques aim the determination of a solution that is closer to the best one. The search space of the optimized solution can be reduced with the use of cardinality constraints, grouping the design variables, which may be extremely convenient. The present study aims to minimize the cost of reinforced concrete frames, using as variables the cross sections of beams and columns, through the heuristic optimization process, and by the usage of cardinality constraints. With this in mind, a previously developed software was improved, which associates the analysis and the dimensioning of reinforced concrete plane frames with the Harmony Search optimization method. In addition to the automatic grouping of the elements, an update was made to a new Brazilian structure sizing standard, NBR 6118: 2014. Some examples of plane frames were analyzed and through the obtained results it was verified the good performance of the adopted method, since the optimized solutions are better or very close to the results obtained by the conventional design of the structures or by other optimization methods.